A proposed strategic make-up plan for the implementation of senior high school in polangui cluster schools, division of camarines norte - Quinto, Alicia Ibita (San Miguel, Iriga City: University of Saint Anthony, 2015)
A proposed strategic make-up plan for the implementation of senior high school in polangui cluster schools, division of camarines.
Includes bibliographical references.
English
Keywords: make-up plan